A Shaking-Culture Method for Generating Bone Marrow Derived Mesenchymal Stromal/Stem Cell-Spheroids With Enhanced Multipotency in vitro - Niibe, Kunimichi; Ohori-Morita, Yumi; Zhang, Maolin; Mabuchi, Yo; Matsuzaki, Yumi; Egusa, Hiroshi (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stromal/stem cells (MSCs), which generally expand into adherent monolayers, readily lose their proliferative and multilineage potential following repeated passages. Floating culture systems can be used to generate MSC spheroids, which are expected to overcome limitations associated with conventional adherent cultures while facilitating scaffold-free cell transplantation. However, the phenotypic characteristics of spheroids after long-term culture are unknown. In addition, regenerative therapies require new culture systems to maintain their undifferentiated state. In this study, we established a novel culture method employing three-dimensional (3D) “shaking” to generate MSC spheroids using bone marrow derived MSCs. Floating 3D cultures of mouse or human MSCs formed spheroids after shaking (85–95 rpm), within 1 month. These spheroids maintained their osteogenic-, adipogenic-, and chondrogenic-differentiation capacity. The adipogenic-differentiation capacity of adherent cultured mouse and human MSCs, which is lost following several passages, was remarkedly restored by shaking-culture. Notably, human MSC spheroids exhibited a renewable “undifferentiated MSC-pool” property, wherein undifferentiated MSCs grew from spheroids seeded repeatedly on a plastic culture dish. These data suggest that the shaking-culture method maintains and restores multipotency that is lost following monolayer expansion and thereby shows potential as a promising strategy for regenerative therapies with mesenchymal tissues.